Attractiveness is Influenced by the Relationship between Postures of the Viewer and the Viewed Person. (May 2013) - Bertamini, Marco; Byrne, Christopher; Bennett, Kate M.
Many factors influence physical attractiveness, including degree of symmetry and relative length of legs. We asked a sample of 112 young adults to rate the attractiveness of computer-generated female bodies that varied in terms of symmetry and leg-to-body ratio. These effects were confirmed. However, we also varied whether the person in the image was shown sitting or standing. Half of the participants were tested standing and the other half sitting. The difference in the posture of the participants increased the perceived attractiveness of the images sharing the same posture, despite the fact that participants were unaware that their posture was relevant for the experiment. We conclude that our findings extend the role of embodied simulation in social cognition to perception of attractiveness from static images.